How to understand sports and traditional games and how to apply it to physical education. On the “Goal of Game” - Ribas, J. P.; Hernández-Moreno, J.; Díaz-Díaz, R.; Borges-Hernández, P. J.; Ruiz-Omeñaca, J. V.; Jaqueira, A. R. (Frontiers in Sports and Active Living, 2023)
Introduction: Does philosopher's stone exist in physical education? It could be said that teaching games for understanding approach (TGfU) keeps turning everything it touches into gold: its presence in the educational centers, its volume of publications, the way of teaching games and sports, its connections with other approaches, its four game categories, learning transferable principles of play. But… no, all that glitters is not gold. There are TGfU issues that should be improved. For example, four categories are insufficient to achieve a diversity of learning experiences that affect the different spheres of the student (affective, cognitive, motor and relational). These categories are even disconnected from each other because TGfU lacks classification criterion. The "goal of game” is a concept that has been studied, but it has not been applied to physical education. The aim of the article is to show how to deepen the understanding sports and traditional games from the “goal of game”, and to propose its applicability to physical education. Methods: The traits of "goal of game" will be identified by investigating two close concepts, "prelusory goal" (philosophy of sport) and "motor-goal" (motor praxeology). Results: 1) to identify the traits of "goal of game" concept (main-motor-problem, described in the game rules and that the players will try to solve during the game dynamics) and its possibilities for understanding traditional games and sports; 2) to the classification of traditional games and sports from “goals of game” and that can be useful to organize the physical education program; 3) to deepen the understanding of sporting games and their applicability to physical education: on the one hand, proposing progressively more specific goal of game options and, on the other hand, proposing a network model of intentions of play to understand the game dynamics. The conclusions collect some properties of the “goal of game” concept in order to be applied in physical education students learning: identify and compare the main-motor-problems of the games, solve these problems and transfer the procedures used to other games. The goal(d) of game amazes us; maybe physical education teachers are curious to continue discovering this wonderful treasure.